Analysis of Twitter's Function as a Media communication of Public Transportation - Mohammad Jafar Loilatu; Bambang Irawan; Salahudin Salahudin; Iradhad Taqwa Sihidi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
Social media plays a significant role in public services, one of which is public transport, while social media often promotes active participation and makes cities more adaptive by using social media. Public transport in Jakarta uses social media as a form of public contact in the provision of services. This study looks at the role of Jakarta's transport social media in delivering excellent information, this research looks at social media twitter accounts consisting of Mass Rapid Transit (MRT), Light Rapid Transit (LRT) and Bus Rapid Transit (BRT) accounts. The method used in this research is a quantitative approach to text analysis focused on Nvivo analysis methods. The phases of analysis using Nvivo begin with: (1) collection data, (2) import data, (3) coding data, (4) data classification, and (5) display data. The findings of this study replied that the social media twitter role in public transport in Jakarta has information features such as: disability rights information, route changes, traffic jams and services. The information provided by the MRT, LRT and BRT twitter social media accounts depends on the activeness of the Twitter social media so that the information can be acknowledged by users of public transport. The flow of information generated by the MRT, LRT and BRT social media accounts through; (1) data sources, (2) collection data, (3) responses, and (4) public information provided by each Twitter account. Media sosial memiliki peran yang besar dalam pelayanan publik salah satunya transportasi publik, media sosial juga mendorong interaksi menjadi aktif dan menjadikan kota lebih adaptif dengan menggunakan media sosial. Transportasi publik Jakarta menggunakan media sosial sebagai alat komunikasi publik dalam memberikan pelayanan. Penelitian ini melihat fungsi media sosial transportasi Jakarta dalam memberikan informasi pelayanan, analisis ini melihat akun media sosial twitter yang terdiri dari akun Mass Rapid Transit (MRT), Light Rapid Transit (LRT) dan Bus Rapid Transit (BRT). Metode dalam penelitian ini menggunakan pendekatan kuantitatif text analysisberbasis software dengan tools analisis Nvivo. Tahapan analisis menggunakan Nvivo dimulai dengan; (1) capturing data, (2) import data, (3) coding data, (4) klasifikasi data, dan (5) display data. Hasil dari penelitian ini menjawab bahwa fungsi media sosial twitter pada transportasi publik Jakarta memiliki karakteristik informasi seperti; informasi tentang hak disabilitas, perubahan rute, kemacetan, dan pelayanan. Informasi yang diberikan oleh akun media sosial twitter MRT, LRT, dan BRT bergantung pada keaktifan media sosial twitter, sehingga informasi tersebut dapat diterima oleh pengguna transportasi publik. Alur informasi yang disampaikan oleh akun media sosial MRT, LRT dan BRT melalui; (1) data sources, (2) processing data, (3) respon dan (4) informasi publik yang disampaikan oleh masing-masing akun twitter.